NOD2 polymorphisms associated with cancer risk: a meta-analysis. - Jingwei Liu; Caiyun He; Qian Xu; Chengzhong Xing; Yuan Yuan (PLoS ONE)
Background Emerging evidence indicated that common polymorphisms of NOD2 might impact individual susceptibility to cancer. However, the results from published studies were inconclusive. The aim of this meta-analysis was to elucidate whether NOD2 polymorphisms were associated with cancer risk. Methods A systematically literature search was performed by using electronic databases including PubMed and Web of Science. ORs and their 95% CI were used to assess the strength of association between NOD2 gene polymorphisms and cancer risks. Results Thirty case-control studies were included in this meta-analysis. The pooled analysis indicated that NOD2 rs2066842 C/T polymorphism was not significantly associated with cancer risk; for NOD2 rs2066844 C/T polymorphism, (TT+CT) genotype was associated with increased cancer risk compared with wild-type CC genotype (OR = 1.32, 95% CI = 1.01-1.72, P = 0.041); for NOD2 rs2066845 C/G polymorphism, individuals with (CC+CG) genotype were significantly associated with increased cancer risk compared with GG genotype (OR = 1.32, 95% CI = 1.01-1.72, P = 0.040); for NOD2 rs2066847 (3020insC) polymorphism, carriers of (insC/insC+insC/-) genotype were significantly associated with increased cancer risk compared with -/- carriers (OR = 1.23, 95% CI = 1.10-1.38, P<0.001). In the subgroup analysis of cancer type, (insC/insC+insC/-) genotype was significantly associated with increased risk of colorectal cancer, gastric cancer and MALT lymphoma, breast cancer, lung cancer, laryngeal cancer but not with urogenital cancer, pancreatic cancer, melanoma or non-Hodgkin lymphoma. Conclusion NOD2 rs2066844 C/T, rs2066845 C/G and rs2066847 (3020insC) polymorphisms might be associated with increased cancer risk. No significant association was observed between NOD2 rs2066842 C/T polymorphism and cancer risk. Further large-scale and well-designed studies are still needed to confirm the results of our meta-analysis.